PENGARUH JENIS PELARUT TERHADAP KANDUNGAN SENYAWA KURKUMIN DAN AKTIVITAS ANTIOKSIDAN EKSTRAK KUNYIT (Curcuma domestica Val.) - Eka Putri Wahyuningtyas, Sasy; Mayun Permana, I Dewa Gede; Sri Wiadnyani, AAI. (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
This research was conducted to determine effect of type of solvent to curcumin content and antioxidant activity of turmeric extract. The experimental design used in this study a randomized block design with 4 different types of solvent (96% ethanol, 95% methanol, acetone 90% and isopropanol 96%). The whole treatment was repeated four times to get 16 results of experimental. Data were analyzed by analysis of variance (ANOVA) and if treatments have effect on the observed parameters, followed by Duncan test. Parameters observed were yield, curcumin content, total phenols, antioxidant capacity, and antioxidant activity.The results showed that the type of solvent significant effect on curcumin content, total phenols, antioxidant capacity and antioxidant activity, but did not significantly effect the yield. Solvent of ethanol showed the best results with the yield of 14.90%, curcumin content of 1.90%, total phenols of 51.56 mg GAE/100 g sampels, the antioxidant capacity of 5.49 mg GAEAC/100 g sampels, and antioxidant activity (IC 50) of 51.17 mg/l.